An affair of online learning and Covid-19 - Mohd Zani, Amirudin; Setia, Roszainora (Fakulti Pengurusan Perniagaan, UiTM Terengganu, 2022)
The outbreak of Covid-19 began in Wuhan, China in December 2019. It then started to spread widely and furiously, causing a shock to the whole world. It was soon declared as the Public Health Emergency of International Concern by the World Health Organization (WHO) on the 30th of January, 2020. WHO labelled the Covid-19 outbreak a global pandemic on March 11,2020 whilst Malaysia confirmed its first case earlier on, with a 41 -year-old man infected with Covid-19, on February 4, 2020 (Elengoe, 2020).